UiTM and MACEE collaborate to expand fulbright and exchange opportunities - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
Universiti Teknologi MARA (UITM) and the Malaysian-American Commission on Educational Exchange (MACEE) officially signed a Memorandum of Understanding (MoU) at UITM Shah Alam, marking a significant milestone in strengthening academic and educational ties between Malaysia and the United States. This collaboration aims to enhance opportunities for student and faculty exchanges, joint research initiatives, and academic mobility programs, particularly through the prestigious Fulbright Program facilitated by MACEE. The MoU reflects a shared commitment to promoting educational diplomacy, fostering cross-cultural understanding. and expanding global academic networks. As MACEE cclebrates its 60th TAASTAIKE MAILA anniversary, this partnership with UITM is part of a broader initiative involving multiple Malaysian universities to deepen engagement with U.S. institutions. Both parties expressed optimism that this collaboration will empower the next generation of scholars and students to pursue excellence through international exposure and collaborative learning.